Security in Media Governing System - Georgy Valeryevich Alekseev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Information security and freedom of speech are making the issue of state media governing rather controversial subject of scientific research. Comparative analysis of the professional journalistic approaches to information security aimed at improving the state policy in the sphere of public institution’s interaction with the media. Security in the media system is a key interest of the professional community of journalists; so standards of self-regulating press require a common social effort on neutralization of the threats to information security in the sphere of mass communications. The main threat to Russia’s national information security is the poor quality of the national media, which may occur due to the restrictions of freedom of speech as well as because of the abuse of such freedom by mass-media. The interests of the state and civil society require the consolidation efforts in creating an enabling social environment for the growth of the prestige and quality of national mass-media, its economic autonomy and political responsibility.